2022
DOI: 10.3390/toxics10110684
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Birth Weight and Exposure to Per- and Polyfluoroalkyl Substances: A Review of Possible Underlying Mechanisms Using the AOP-HelpFinder

Abstract: Prenatal exposure to per- and polyfluorinated substances (PFAS) may impair fetal growth. Our knowledge of the underlying mechanisms is incomplete. We used the Adverse Outcome Pathway (AOP)-helpFinder tool to search PubMed for studies published until March 2021 that examined PFAS exposure in relation to birth weight, oxidative stress, hormones/hormone receptors, or growth signaling pathways. Of these 1880 articles, 106 experimental studies remained after abstract screening. One clear finding is that PFAS are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 207 publications
(167 reference statements)
0
11
0
Order By: Relevance
“…There is an AOP for human developmental neurotoxicity based on binding to transthyretin (https://aopwiki.org/aops/152) that rates the evidence for PFAS as moderate. In a literature search for factors related to PFAS and lower birthweight (Gundacker et al, 2022), effects on thyroid hormones were a consistent finding.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…There is an AOP for human developmental neurotoxicity based on binding to transthyretin (https://aopwiki.org/aops/152) that rates the evidence for PFAS as moderate. In a literature search for factors related to PFAS and lower birthweight (Gundacker et al, 2022), effects on thyroid hormones were a consistent finding.…”
Section: Resultsmentioning
confidence: 85%
“…Given the different search terms and species included, these findings in common with our AOP network are encouraging. Gundacker et al (2022) also found associations with oxidative stress and estrogenic effects. Oxidative stress is a common finding in stressed cells and tissues and could be affecting multiple KEs in our AOP network, but we did not find it to be a discreet KE at a specific time in our AOPs.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations